A Randomized Controlled Study to Evaluate the Effectiveness of 2 Treatment Methods in Reducing Incidence of Short Peripheral Catheter-Related Phlebitis. Issue 2 (March 2018) - Gunasegaran, Nanthakumahrie; See, Min Ting Alicia; Leong, Siew Teing; Yuan, Long Xia; Ang, Shin Yuh
Abstract : Short peripheral catheter (SPC)-related phlebitis can lead to bloodstream infections and affect patients' quality of life. A randomized trial was carried out to evaluate the effectiveness of 2 treatment methods in reducing the incidence of SPC-related phlebitis. The 2 treatment methods differed in terms of the cleansing solution used before insertion and dressing material used after removal. The results demonstrated that the type of cleansing solution and postremoval dressing material did not make a difference in the incidence of phlebitis. Strict adherence to aseptic techniques and prompt removal of the SPC remained the cornerstone in the prevention of phlebitis.